Coexisting Type 1 Diabetes, Persistent Symptoms, and Financial Issues Associate With Poorer Adherence to a Gluten-Free Diet in Celiac Disease After Transition From Pediatrics to Adult Care - Kivelä, Laura; Eurén, Anna; Repo, Marleena; Huhtala, Heini; Kaukinen, Katri; Kurppa, Kalle (Frontiers in Nutrition, 2022)
Purpose: We evaluated adherence to a gluten-free diet and associated factors in adult celiac disease patients diagnosed in childhood. Methods: Comprehensive medical data on 955 pediatric celiac disease patients was collected and study questionnaires sent to 559 who were now adults. All variables were compared between strictly adherent and non-adherent patients. Results: Altogether 237 adults (median age 27 years, 69% women) responded to the questionnaires a median of 18 (range 3–51) years after the childhood diagnosis. Altogether 78% were reportedly adherent and 22% non-adherent. The non-adherent patients had more concomitant type 1 diabetes (18% vs. 4%, p=0.003), whereas the groups did not differ in demographic data or clinical and histological features at diagnosis, or in short-term dietary adherence. In adulthood, non-adherent patients found gluten-free diet more challenging (39% vs. 17%, p<0.001) and had higher prevalence (39% vs. 19%, p=0.004) and severity of symptoms. The main motivation factors for dietary adherence were attempts to avoid symptoms and complications, but these were considered less important and financial issues more important among non-adherent patients. Adherent and non-adherent patients did not differ in socioeconomic or lifestyle factors, comorbidities other than type 1 diabetes, self-reported general health, health concerns, follow-up, or in quality of life. Conclusion: Most originally pediatric celiac disease patients reported strict dietary adherence in adulthood. However, particularly those with concomitant type 1 diabetes require attention during the transition from pediatric to adult care. Recognizing patients’ personal motivations regarding the diet could also help to improve long-term treatment and health outcomes.